Modélisation de l'écophysiologie de l'huître Crassostrea gigas dans un environnement estuarien - Barille, Laurent; Heral, Maurice; Barilleboyer, Al (Gauthier-villars, 1997)
An ecophysiological deterministic model of growth, reproduction and interactions between the bivalve and its estuarine environ ment was established for the Japanese oyster Crassostrea gigas. The environmental variables used in the model are: total particulate matter, particulate organic matter, particulate inorganic matter, chlorophyll, phaeopigments, proteins, lipids and carbohydrates. Rates of clearance, filtration, ingestion, absorption and respiration along with efficiencies of retention, selection and absorption are modelled with endogenous (dry weight of the animal, energy allocation between growth and reproduction) and exogenous variables (temperature, food quality and quantity). The model simulate the temporal evolution of two compartments: somatic and storage-gonad. Absorbed energy is allocated to soma up to a maximum somatic growth. This maximum decreases with age and never exceeds 0.02 g.d-1 .oyster-1. Energy in excess is allocated to the storage-gonad compartment. The model identify storage and gametogenesis periods and correctly predicts spawning intensity. In this model, the oyster selectively reject inorganic from organic particles, enriching the ingested ration. Within potentially nutritive particles, fewer particles containing phytopigments are rejected compared with detritic particles. Absorption efficiency is represented as a function of organic content in the ingested ration. Microphytes are absorbed with an efficiency which fluctuates from 20 to 60%. The model predicts negative absorption for detritic material to take into account metabolic faecal losses. Theses formulations provide information about the temporal evolution of the amount of microphytes and detritic matter biodeposited as pseudofaeces and faeces. Un modèle écophysiologique déterministe de la croissance, de la reproduction et des interactions entre le bivalve et son environnement estuarien a été élaboré pour l'huître japonaise Crassostrea gigas. Pour fonctionner, le modèle a besoin de la température de l'eau, des ...